Pelaksanaan Program Pendekatan Keagamaan melalui KKN STIBA Makassar di Desa Baruga Kabupaten Maros - Asnawati Patuti; Rahmat Rahmat (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2020)
Baruga village, Bantimurung sub-district is an area in Maros district where the majority of the original population is Muslim. The existence of Islam in Maros has been around for a long time, namely with the entry of Raja Gowa and Tallo which have a direct border area with the Marusu Maros kingdom so that the Islamic life of the Baruga Village Community, Bantimurung Maros sub-district looks so real. The purpose of Real Work Lecture (KKN) III Stiba Makassar is to realize community service which is one of the pillars of the tri dharma of higher education. The method of implementing this program begins with conducting a field review based on an independent instrument. The results of the KKN program show the importance of community service programs by seeing the benefits felt by KKN participants, the community and the government. Religious activities which are the main orientation of this program have been successfully carried out, as well as social activities, organizational activities and the active role of KKN participants with the government in successful community development efforts.